2022
DOI: 10.1111/famp.12832
|View full text |Cite
|
Sign up to set email alerts
|

Open dialogue trainees' perspectives on learning processes and psychotherapeutic practice: A prospective focus group study

Abstract: Open Dialogue is a collaborative approach to mental health care emphasizing integrated services and a dialogical psychotherapy approach. Open Dialogue training programs eschew traditional didactic teaching of technical therapeutic skills in favor of more experiential learning processes. It is unclear how these training programs affect trainees and shape their perspectives on Open Dialogue. Our aim was to follow up a group of Australian Open Dialogue trainees and explore their perspectives on learning processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Buus et al. (2022) reported on the evaluation outcomes of two overlapping Open Dialogue courses held in Sydney in 2017. The courses lasted for between 2 and 3 years depending on previous experience of participants and had low sample sizes of between three and six participants at different points due to participant attrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Buus et al. (2022) reported on the evaluation outcomes of two overlapping Open Dialogue courses held in Sydney in 2017. The courses lasted for between 2 and 3 years depending on previous experience of participants and had low sample sizes of between three and six participants at different points due to participant attrition.…”
Section: Resultsmentioning
confidence: 99%
“…What does come forward from reading the literature is that Open Dialogue education practices have a non‐structured approach that participants in training find difficult to engage with (Buus et al., 2022). And consumers as well as family networks have reported that they find the non‐structured approach and lack of willingness to discuss medication as well as prognosis frustrating (Dawson et al., 2022).…”
Section: Discussionmentioning
confidence: 99%